Structure Design and Mobility Analysis of a Climbing Robot. (May 2020) - Li, Xiaohu; Cao, Hongxin; Feng, Song; Xie, Chao
Abstract: RiSE and LEMUR IIB have good climbing ability. Inspired by these two robots, a new climbing robot with simplified motion mode and strong load capacity is proposed. In this paper, the structure of the robot is introduced detailedly. Through the dynamic analysis of its leg and body, the torque of the traction and swing motor under various driving modes are obtained. Static analysis of the robot's claw is also carried out during the climbing process. Meanwhile, the equivalent tangential force and normal force required for the claw attached to the wall are described. The results indicate that the robot has high mobility and can successfully realize the climbing movement.